2022
DOI: 10.3991/ijet.v17i01.26857
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serious Game on the Nursing Students' Learning, Behavioral Engagement, and Motivation

Abstract: Digital game-based learning is a ludic approach that has evolved through the development of information and communication technologies (ICT), making the learner an active participant in the virtual learning environment instead of a mere observer. It is an electronic simulation tool suitable for improving learning efficiency as well as learner engagement and motivation. The integration of this educational technology in the teaching and learning process can contribute to the construction of knowledge, the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Researchers have also focused on the use of serious games as facilitators of education in large groups [ 51 53 ]. Serious games have been shown to enhance practical and procedural abilities among nursing students by offering them an immersive and secure setting for improving their clinical reasoning and decision-making capabilities [ 54 ]. Nursing educators are encouraged to use SGs to enhance cognitive skills and attention, improve judgment, foster time-efficient decision-making, facilitate safe decision practices, and promote decision exploration [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also focused on the use of serious games as facilitators of education in large groups [ 51 53 ]. Serious games have been shown to enhance practical and procedural abilities among nursing students by offering them an immersive and secure setting for improving their clinical reasoning and decision-making capabilities [ 54 ]. Nursing educators are encouraged to use SGs to enhance cognitive skills and attention, improve judgment, foster time-efficient decision-making, facilitate safe decision practices, and promote decision exploration [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, similar to the literature, it was determined that students' score for the motivation factor and motivation scale was above normal. İdrissi et al reported that motivation of students who serious game on the learning of nursing care in pediatrics effected [29]. Kang and Suh stated that the application was useful to students [2], they could follow the patient and learn while having fun.…”
Section: Student's Interviewsmentioning
confidence: 99%
“…Uma das alternativas para enfrentar essa dificuldade é o emprego de instrumentos de gamificação e de jogos sérios nos processos de treinamento e desenvolvimento organizacional. Essas estratégias têm sido reconhecidas como uma contribuição para o desenvolvimento dos profissionais, particularmente no que diz respeito ao desenvolvimento de conhecimentos, habilidades e atitudes, ou seja, elementos mobilizados que compõem as competências (Allal-Chérif, Bidan & Makhlouf, 2016;El Idrissi, Chemsi, El Kababi & Radid, 2022;Gurbuz & Celik, 2022;Jaunay et al, 2019;Le Boterf, 1995;Mason & Loader, 2019;Michael & Chen, 2006;Miguel, Lage & Galindez, 2020;Ypsilanti, Vivas, Räisänen, Viitala, Ijäs & Ropes, 2014). Por isso, a gamificação e os jogos sérios têm sido considerados ferramentas relevantes para programas de treinamento e desenvolvimento, especialmente em áreas sensíveis, como a interação homem-computador (Armstrong, Landers & Collmus, 2016;Armstrong & Landers, 2018;Deterding, 2018;Landers, 2018;van Bree, 2014).…”
Section: Introductionunclassified